Waste Management at the Bahteramas Regional General Hospital in Southeast Sulawesi Province During the COVID-19 Pandemic - Tosepu, Ramadhan; Ode Ratna, Wa; Setiawan, Harry; Waluyo, Budi; ., Indrawati (KnE Social Sciences, 2023)
Hospitals produce large amounts of wastewater and biomedical waste, which contain various contaminants and, if not treated, negatively impact the environment. Over the last two years, the COVID-19 outbreak increased hospital waste stockpiles because treating patients needed more medical equipment. Bahteramas Regional General Hospital generated 9,923 kg of medical waste in 2020 and 9,577 kg in 2021. From this data, it was possible to see that the amount of waste decreased from 2020 to 2021. This study aimed to determine how medical waste was processed at the Bahteramas Regional General Hospital in Southeast Sulawesi Province during the COVID-19 pandemic. This survey was conducted at the Bahteramas Regional General Hospital in Southeast Sulawesi, using report data on medical waste and Covid-19 waste. According to the findings of this study, medical hazardous and toxic waste management was carried out, including separation, labeling, transportation, storage, disposal/destruction, and the use of third parties in final disposal. Meanwhile, sampling was used to determine the feasibility of processing liquid waste before it was distributed to the Water Agency. Keywords: Hospital, Medical Waste, Covid-19